2010
DOI: 10.1159/000294277
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Genetic Testing Research Varies by Social Group

Abstract: Background: Advances in technology have made individual access to personal genetic information foreseeable in the near future. Policy makers and the media forecast that the ready availability of personal genetic profiles would benefit both the individual and the health care system by improving outcomes and decreasing cost. However, there is a significant gap between having access to genetic data and either wanting or understanding the information it provides. Objective: Our primary aim was to evaluate, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 41 publications
3
97
1
Order By: Relevance
“…Receipt of genetic disease risks has not been reported to cause long-term psychological harms 30,31 , suggesting that individuals interested in learning about their genomic risks are better able or prepared to manage the information. Physician involvement may be critical to ameliorating concerns about test results as another study reported nearly half of individuals surveyed who had undergone DTC testing had concerns about the testing process/experience 33 . Although we were not able to assess characteristics of patients who underwent testing, prior studies have reported that individuals who are interested or have undergone genomic risk profiling tend to be White and have at least some college education [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Receipt of genetic disease risks has not been reported to cause long-term psychological harms 30,31 , suggesting that individuals interested in learning about their genomic risks are better able or prepared to manage the information. Physician involvement may be critical to ameliorating concerns about test results as another study reported nearly half of individuals surveyed who had undergone DTC testing had concerns about the testing process/experience 33 . Although we were not able to assess characteristics of patients who underwent testing, prior studies have reported that individuals who are interested or have undergone genomic risk profiling tend to be White and have at least some college education [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Factors suggested as possible reasons for lower uptake among racial minorities include decreased referral from minority-serving physicians (Shields et al 2008), lower rates of health insurance (Armstrong et al 2006), medical distrust (Armstrong et al 2008), and concerns about potential harm (Catz et al 2005). Scarce literature exists on racial minorities' engagement with DTC-PGT (Hensley Alford et al 2011;Bloss et al 2010); although a number of population surveys have reported lower levels of DTC-PGT awareness among racial minority groups (Ortiz et al 2011;Kolor et al 2012;Finney Rutten et al 2012;Agurs-Collins et al 2015;Langford et al 2012). When compared to Whites, however, differences in awareness have not consistently been statistically significant (Finney Rutten et al 2012;Agurs-Collins et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Only two previous studies that offered DTC-PGT as part of study participation evaluated differences in uptake by racial group, and each reported that Whites may be more likely to undergo DTC-PGT than non-Whites (Hensley Alford et al 2011). In the multiplex study, participants were offered free genetic risk information for eight common complex conditions (Hensley Alford et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly for prevention, interest in genetic susceptibility testing in the present study was not lower among those at greater risk for chronic disease and, indeed, was higher for those with a family history of chronic disease and those in high-risk race/ethnic groups (Hispanics and non-Hispanic blacks). This racial difference is particularly intriguing in light of prior work showing that AfricanAmericans might be less interested in genetic susceptibility testing (Hipps et al 2003) and be less likely to participate in genetic susceptibility testing research (Hensley Alford et al 2011). Interest in genetic testing may correlate with behavior change , and, similar to previous research (McGuire et al 2009), we found that about 80 % of young adults anticipated being more likely to improve their diets and physical activity patterns in response to higher genetic susceptibility results for heart disease, type 2 diabetes, and stroke.…”
Section: Discussionmentioning
confidence: 99%